CO2 capture and in-situ conversion to organic molecules - Lan Zhao; Hai-Yang Hu; An-Guo Wu; Alexander O. Terent’ev; Liang-Nian He; Hong-Ru Li (Journal of CO2 Utilization, 2024)
To address the CO2 accumulation in atmosphere, various initiatives have been proposed, among which CO2 capture and utilization (CCU) is regarded as an appealing strategy to reconcile carbon emission and resource utilization. Especially, integrated CO2 capture and utilization (ICCU), i.e. performing CO2 capture and in-situ conversion can circumvent the energy-intensive CO2 desorption step and thus facilitate establishing step- and energy-efficient process, rendering the conversion at mild conditions particularly at low pressure due to substantial activation upon CO2 uptake. However, CO2 capture and in-situ conversion is not the simple add-up of these two processes. Its successful implementation relies on the harmonization of CO2 capture reagents, substrates and the corresponding catalysts. By far, tremendous efforts have been made in this field and a plethora of CO2 capture reagents including inorganic bases, organic bases, ionic liquids and carbonaceous materials have been utilized to capture CO2 and the conversion protocols such as hydrogenation, cycloaddition, carboxylative cyclization etc. have been explored for these captured CO2. As a result, the valuable products containing methanol, methane, carbonates, carbamates, oxazolidinones, ureas, and quinazolinone have been obtained from CO2 and more importantly, the CO2 chemistry theory is also enriched via investigating the structure and reactivity of the captured CO2 in various reactions. In this review, we summarize the progress on CO2 capture and in-situ conversion based on the reaction types and corresponding CO2 absorbents. It’s hoped that this review can shed light on the design of CO2 capture and in-situ conversion and inspire the further development of this field.